2007
DOI: 10.1016/j.shpsb.2006.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The connection between logical and thermodynamic irreversibility

Abstract: There has recently been a good deal of controversy about Landauer's Principle, which is often stated as follows: The erasure of one bit of information in a computational device is necessarily accompanied by a generation of kT ln 2 heat. This is often generalised to the claim that any logically irreversible operation cannot be implemented in a thermodynamically reversible way. John Norton (2005) and Owen Maroney (2005) both argue that Landauer's Principle has not been shown to hold in general, and Maroney offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 18 publications
1
67
0
Order By: Relevance
“…Landauer's principle is fully compatible with the laws of thermodynamics [9], [11][12][13][14]. Indeed Landauer's principle has been used to reconcile the operation of Maxwell's Demon with the second law of thermodynamics.…”
Section: Applying Landauer's Principle To the Universementioning
confidence: 99%
“…Landauer's principle is fully compatible with the laws of thermodynamics [9], [11][12][13][14]. Indeed Landauer's principle has been used to reconcile the operation of Maxwell's Demon with the second law of thermodynamics.…”
Section: Applying Landauer's Principle To the Universementioning
confidence: 99%
“…It also exposed deficiencies in the extant discussions of LP in the wider literature, demonstrated that LP could not be established by reasoning about particular cases, and showed that a general proof of LP had not been given. Ladyman et al (2007), hereafter LPSG, proposed a model of the implementation of logical operations by physical processes in order to clarify the exact statement of LP, and then offered a new proof of the latter based on the construction of a thermodynamic cycle, arguing that if LP were false it would be possible to harness a machine that violated it to produce a violation of the second law of thermodynamics. In a recent paper in this journal (2011), John Norton directly challenges the consistency of that proof.…”
Section: Introductionmentioning
confidence: 99%
“…It is no small undertaking, since a change to the fundamental law must be propagated consistently through all of thermodynamics. See Ladyman et al [30,31]. The challenge is a worthy one and they have made a quite creditable effort.…”
Section: Problem 3: Failure Of Demonstrations Of Landauer's Principlementioning
confidence: 99%
“…For completeness, from (32) and (28), the thermodynamic entropy created in the case of the 5 g bead for n = 10 is k(n − 1)m(2.3026) = 62.2 k. From (30), the thermodynamic entropy created in the release of the 100 amu bead for n = 10 is k ln 9 = 2.197 k. The first entropy creation is significantly larger since the process recompresses the bead location to the final state, by a less efficient means.…”
Section: The Driven Bead At Molecular and Macroscopic Scalesmentioning
confidence: 99%